CONTENT AND ORGANIZATION FORMS OF CONTINUOUS PROFESSIONAL DEVELOPMENT OF TEACHERS IN DEVELOPED COUNTRIES (World Bulletin of Social Sciences, 2023)
This article analyzes the specific features, content, and organizational forms of the system of professional development of pedagogues in developed countries, especially the United States. At the same time, there are detailed opinions about the fact that today in the leading countries of the world, the system of continuous training of teachers has been abandoned and the system of continuous training has been introduced